2017
DOI: 10.1159/000477454
|View full text |Cite
|
Sign up to set email alerts
|

Elimination Rates of Electrolytes, Vitamins, and Trace Elements during Continuous Renal Replacement Therapy with Citrate Continuous Veno-Venous Hemodialysis: Influence of Filter Lifetime

Abstract: Background/Aims: During continuous renal replacement therapy, relevant losses of nutritional substrates, vitamins, and trace elements via the filter may occur. We investigated filter lifetime efficiency during a 72-h treatment period. Methods: This prospective study included 40 patients undergoing citrate continuous veno-venous hemodialysis (CVVHD). The elimination rates were measured at 24, 48, and 72 h. To assess the influence of filter lifetime, we determined substrate loss every 24 h over a 72-h interval. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The same group reported the depletion effect of CRRT on Cu and Se during a case of prolonged CRRT confirming, resulting in life-threatening complications [ 13 ]. In their first study, Datzmann et al [ 14 ] detected zinc, but no copper, but could not find significant Zn losses in their second study [ 15 ]. Pasko et al detected Cu, Se, Mn Se and Zn in effluent of children undergoing RRT (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same group reported the depletion effect of CRRT on Cu and Se during a case of prolonged CRRT confirming, resulting in life-threatening complications [ 13 ]. In their first study, Datzmann et al [ 14 ] detected zinc, but no copper, but could not find significant Zn losses in their second study [ 15 ]. Pasko et al detected Cu, Se, Mn Se and Zn in effluent of children undergoing RRT (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent showed losses of vitamin C [ 9 ▪▪ , 19 ▪▪ ] but B1, B6, B12, D2, D3 could not be detected [ 19 ▪▪ ]. Searching for vitamins A, B9, B12 and E, Datzmann et al could not detect any in effluent fluid [ 14 , 15 ]. Similarly, Story et al found that vitamin C was detectable in the effluent, but vitamin E was not (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of these alterations in micronutrients are not clear, but their impact on outcomes in pediatric ECMO may be important and require further investigation. In patients receiving ECMO who also require dialysis, micronutrient losses may be further compounded, because continuous renal replacement therapy has been associated with loss of ionized calcium, inorganic phosphorus, and selenium, among other trace elements . These observations may have implications for micronutrient supplementation in the pediatric ECMO population, and attempts to monitor micronutrients should be made.…”
Section: Nutrition Requirements During Pediatric Ecmomentioning
confidence: 99%